Tumors of the Central Nervous System Primary and Secondary - Roy Morgan, Lee (IntechOpen, 2014)
A novel concept that is reviewed and discussed in several chapters in the book alludes to the transport of drugs bound to red blood cells into the highly vascular CNS tumors - both primary and metastatic. Such a transport mechanism is unique and of significant therapeutic potential. It is hopeful that the novel information presented in this book will result in new approaches to the treatment CNS tumors.